GREEN TIME AND CYCLE TIME OPTIMIZATION AT AN INTERSECTION USING ARTIFICIAL BEE COLONY (ABC) - ISTIQOMAH (NIM: 23815005), NOVERA
Traffic congestion is one of the main problems in big cities. The congestion is caused by the increased volume of vehicles that are not balanced by the existing highway capacity. To overcome this, a traffic control system is needed to minimize the congestion. In this study, traffic control system and all phenomena of traffic are simulated by Vissim commercial software that integrated with Matlab commercial software. Optimization algorithm is applied to Matlab to get the optimal green time and cycle time. The optimization algorithm used in this research is Artificial Bee Colony (ABC) algorithm. ABC algorithm is one of the optimization algorithm that adapt honey bee behavior. It has three main components, namely food source, employed foragers, and unemployed foragers. It is used to obtain the optimal green time and cycle time with randomize technique, so it can minimize the total of vehicleÃ‚Â’s queue length from each road arm at an intersection. There are two types of highway design which are used in this study, i.e. main and minor street. The main street has two opposite paths which each path has two lanes, while the minor street has two opposite paths which each path has only a lane. Then, some of network objects in Vissim are arranged, namely vehicle inputs, vehicle routes, and signal heads. Vissim output, the number of vehicle that enter and exit the intersection in every cycle time, is used as an input of objective function in ABC algorithm. The result of optimization, the optimal green time and cycle time, is used as vissim input for simulation running in the next cycle. The simulation result, the sum of vehicles queue length from each arm road, obtained from Vissim and ABC algorithm. Data before and after optimization are compared to determine how much the influence of ABC algorithm in reducing vehicles queue length at intersection. The simulation result shows that ABC algorithm in this research can minimize the queue length of vehicles at intersection.